PREDICTION OF SUCCESSFUL DEFENSE MOVEMENT OF FEMALE HANDBALL PLAYERS - Saša Jovanović,; Saša Marković,; Matej Kleva, (Sport Scientific And Practical Aspects, 2025)
This research aimed to verify and determine the predictive relationships of certain motor and morphological abilities with the execution of specific motor movements of a non-ball slalom and the movement in a triangle. The sample consisted of 20 female respondents, players from Bosnia and Herzegovina Premier League, aged 16-25 years. The predictor variables used were the years of the respondents, height, weight, BMI, fat content, sprint over 30m, SAMO reaction-agility test and Illinois test. The sample of criteria variables consisted of a non-ball slalom and a movement in a triangle. The general results of the regression analysis showed that on the basis of R2 = .876 it can be concluded that the predictor system explains 87.6% of the variability in prediction and shows the statistical significance of p = .000 with the results of the subjects in the motor slalom ball test. From the analysis of the prediction results of the system of predictor variables for the criterion variable of movement in the triangle (R2 = .704), it can be concluded that no statistically significant correlation (p = .133). The results of this study indicate a partially positive predictive value of this predictor set of variables, opening up the space for verification of some other systems of predictor and criterion variables. The second part of the conclusion is that the movements of players in defense can be enhanced by training that will target the development and refinement of speed, agility, and explosive power, taking into account genetic predisposition.